Exploring the lived experience of faculty implementing case-based learning: A phenomenological study - Caroline Delany; Jan Illing; Marie McIlroy; Ronan Daly; Catherine Bruen; Naji Alamuddin; Clare Condron; Martina Crehan; Sally Doherty; Frances Meagher; Gozie Offiah; Sarah O’Neill; et al. (BMC Medical Education)
Abstract Background Case-based learning (CBL) is a useful pedagogical approach, for which learner experience has been well researched. The experience of faculty is less known. CBL was integrated into the first year of a new pre-licensure medical curriculum, so the faculty experience of transition from large group teaching to structured CBL was investigated. Methodology Interpretative phenomenological analysis (IPA) was undertaken to explore the facilitator lived experience through reflective inquiry. Ten CBL facilitators were purposively selected from a diverse pool of faculty using maximum variation; faculty were involved in patient care, research, and education, and were a mix of ages, ethnicities and genders. Semi-structured interviews were conducted and analysed according to the IPA structure. Results Overall experiences were positive. Facilitators repeatedly expressed the enjoyment felt from closer student interaction. They reported that CBL afforded an authentic and active teaching approach. Other themes included: initial uncertainty regarding their role, anxiety around standardisation of the student experience and concerns regarding the level of content expertise required. However, confidence generally improved with experience facilitating. Conclusion These insights provide a deeper understanding of faculty perceptions of the CBL facilitator’s role and will better inform future faculty development initiatives, as well as the iterative design of the CBL teaching resources.